Application service delivery in the modern virtualized data center-improving reliability and scalability - Raza, A; Koondhar, M.Y.; Sindhu, Sindhu; Hyder, M; Menghwar, G.D; Baloch, B; Shah, Asadullah (Science Pakistan, 2016)
Application container virtualization has recently been re-ointroduced as a potential solution for rapid deployment of applications for developers within the ever changing infrastructure landscape. Although, there appears to be ' gap' of when the Application Container, Infrastructure Hypervisor or both technologies should be leveraged to provide for scalability, reliability while improving on overall deployment time. This study is an attempt to review the two technologies and understand thier specific/shared use-cases in order to develop a framework to assist with the decision making model that transforms Technology (IT) professionals within both the applications and infrastructure disciplines can use to determine making model that information Technology (It) professionals within their selection of one environment, diffusion of innovation and process-virtualization.